Cardiovascular risk factors early in the course of treatment in people with type 2 diabetes without established cardiovascular disease: A population‐based observational retrospective cohort study. Issue 3 (2nd October 2021) - Khunti, Kamlesh; Hertz, Christin L.; Husemoen, Lise Lotte N.; Mocevic, Emina; Nordsborg, Rikke B.; Piltoft, Johanne S.; Bain, Stephen C.
Abstract: Aims: To characterise the cardiovascular risk of people with type 2 diabetes without established cardiovascular disease but with risk factors, relative to those with established cardiovascular disease, to provide information on which patients could benefit from early use of glucose‐lowering therapies that also reduce cardiovascular risk. Methods: Data from people with type 2 diabetes initiating second‐line glucose‐lowering medication were retrieved from the UK Clinical Practice Research Datalink GOLD database and linked with Hospital Episode Statistics and Office for National Statistics (2001–2016). Cox proportional hazards models were used to estimate relative risks of major adverse cardiovascular events within groups defined by the presence of selected risk factors in people without versus with established cardiovascular disease. Results: Of 53, 182 individuals, 19.4% had established cardiovascular disease (i.e. a prior cardiovascular event). Over 5–7 years' follow‐up, the rate of major adverse cardiovascular events was 14.0 and 49.6 events/1000 person‐years without and with established cardiovascular disease, respectively (hazard ratio [HR] 0.28, 95% confidence interval [CI] 0.26, 0.29). Compared with a reference HR 1.0 for participants with established cardiovascular disease, estimated glomerular filtration rate <60 mL/min was the single factor associated with the highest risk of major adverse cardiovascular events (HR 0.75, 95% CI 0.70, 0.81) and mortality (HR 1.12, 95% CI 1.07, 1.18) in people with type 2 diabetes without established cardiovascular disease. The combination of chronic kidney disease with older age, smoking and/or dyslipidaemia was associated with a similarly high risk of cardiovascular events in people with type 2 diabetes and without cardiovascular disease compared with those having established cardiovascular disease. Conclusions: These analyses provide important information to identify people who may benefit from primary prevention of cardiovascular disease. Modifiable cardiovascular risk factors should be controlled early in all individuals with type 2 diabetes (as well as in all individuals with cardiovascular disease).